2023
DOI: 10.1007/s10257-023-00625-3
|View full text |Cite
|
Sign up to set email alerts
|

A readiness assessment framework for the adoption of 5G based smart-living services

Abstract: The subject of this article is to analyze the users’ attitude towards new, 5G-enabled smart living services before their commercial launch. The goal is to offer a framework for the analysis and evaluation of influential factors in the early adoption of 5G residential services. Additionally, the paper examines how mobile operators can leverage their existing infrastructure and services to boost the acceptance of both 5G as a technology and the provided smart-living services. To ascertain the potential impact th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…According to 7 , it is crucial to consider particular psychological elements influencing decision-making while considering technology adoption. For a new technology marketing campaign to be successful, researchers advised including these elements 12 , 29 . We, therefore, created a model customized for the requirements of 5G internet technology to aid in the present research.…”
Section: Literature Review With Hypothesis Developmentmentioning
confidence: 99%
“…According to 7 , it is crucial to consider particular psychological elements influencing decision-making while considering technology adoption. For a new technology marketing campaign to be successful, researchers advised including these elements 12 , 29 . We, therefore, created a model customized for the requirements of 5G internet technology to aid in the present research.…”
Section: Literature Review With Hypothesis Developmentmentioning
confidence: 99%
“…They also explore revenuesharing models, such as shared spectrum and NS. For example, the authors in [23] analyze the monetization question to the residential user's segment and address the use of 5G NS capability and appropriate pricing strategies. References [22,24] analyze price and service competition under certain cost modeling assumptions, server capacity, and competition prices where firms compete regarding their prices under service levels.…”
Section: Related Workmentioning
confidence: 99%
“…This includes pricing strategies such as pay-per-use and subscription models, as well as revenue-sharing models such as spectrum sharing and network slicing. Also, in [26], the authors explore how to monetize 5G networks for residential users using network slicing and effective pricing strategies. Our paper provides an economic analysis of URLLC and mMTC services over 5G networks based on previously mentioned studies that have demonstrated the economic feasibility of these services.…”
Section: Related Workmentioning
confidence: 99%